Pengaruh Penggunaan Metode Experiential Learning terhadap Hasil Belajar Anatomi Bagi Mahasiswa Fakultas Kedokteran Universitas Muhammadiyah Semarang - Arfiyanti, Mega Pandu; Dewi, Arum Kartika (Universitas Muhammadiyah Semarang, 2018)
The Influence of the Use of Experiential Learning Methods on Anatomy Learning Outcomes for Students of the Faculty of Medicine, University of Muhammadiyah SemarangBackground: Anatomy is a basic science that must be mastered by students of the Faculty of Medicine as the basis for conducting a physical examination and clinical reasoning. Students' understanding of anatomy is still lacking because they think that anatomy is very difficult to learn. Anatomy active learning method is needed to improve students' understanding.Objectives: The study was to determine the effect of using experiential learning methods on student anatomy learning outcomes.Methods: This study is an experimental pretest posttest design study with a sample of all first year students of Unimus Medical Faculty which were divided into control and treatment groups by randomized sampling. Students in the treatment group were taught anatomy using the experiential learning method, while the control group was taught using the conventional method. The data taken is the mean difference in the pretest posttest scores of the control group and the treatment group.Results: Out of 110 students, only 94 students followed the entire study protocol, consisting of 47 students in the control group and 47 students in the treatment group. Based on the independent t test, the results obtained sig (2-tailed) 0.000, which means that the experiential learning method has an influence on the learning outcomes of anatomy.Conclusion: The experiential learning method is effectively used to improve the anatomy learning outcomes of students of the Faculty of Medicine, University of Muhammadiyah Semarang.Latar belakang: Anatomi merupakan ilmu dasar yang harus dikuasai oleh mahasiswa Fakultas Kedokteran sebagai dasar melakukan pemeriksaan fisik dan penalaran klinis. Pemahaman mahasiswa akan ilmu anatomi masih kurang karena menganggap anatomi sangat susah dipelajari. Metode pembelajaran aktif anatomi diperlukan untuk meningkatkan pemahaman mahasiswa.Tujuan: Penelitian mengetahui pengaruh penggunaan metode experiential learning terhadap hasil belajar anatomi mahasiswa.Metoda: Penelitian ini merupakan penelitian eksperimental pretest posttest design dengan sampel seluruh mahasiswa tahun pertama FK Unimus yang dibagi menjadi kelompok kontrol dan perlakuan dengan randomised sampling. Mahasiswa kelompok perlakuan diajarkan anatomi dengan metode experiential learning, sedangkan kelompok kontrol dengan metode konvensional. Data yang diambil adalah rerata selisih nilai pretest posttest kelompok kontrol dan kelompok perlakuan.Hasil: Dari 110 mahasiswa hanya 94 mahasiswa yang mengikuti seluruh protokol penelitian yang terdiri dari 47 mahasiswa kelompok kontrol dan 47 mahasiswa kelompok perlakuan. Berdasarkan uji independent t test di dapatkan hasil sig (2-tailed) 0.000 yang artinya metode experiential learning memiliki pengaruh terhadap hasil belajar anatomi.Simpulan: Metode experiential learning efektif digunakan untuk meningkat hasil belajar anatomi mahasiswa Fakultas Kedokteran Universitas Muhammadiyah Semarang.